PROSES PEMBERIAN ROYALTI KEPADA AHLI WARIS (PAPA T BOB) BERDASARKAN UNDANG-UNDANG HAK CIPTA - Adelia Permatasari; Rakhmita Desmayanti (Fakultas Hukum Universitas Trisakti, 2021)
Copyright is one of the rights of Intellectual Property Rights. Music/song is one of the works that is protected by copyright. In 2020, a children's songwriter named Papa T Bob died. The mechanism for awarding royalties for a creator who has died is still not clearly explained in Law Number 28 of 2014 concerning Copyright. Because of this, a problem arises in this material, whether the heirs need to be involved when the copyrighted work is used by other people and what is the process for awarding royalties to the heirs of the songwriters (Papa T Bob) based on Law Number 28 of 2014 concerning Copyright. The research method in this study uses normative methods, the nature of the research is descriptive-analytic with qualitative data analysis and draws conclusions using the deductive method. The results of the study illustrate that an heir needs to be involved if the copyrighted work is used for economic interests based on article 16 paragraph 2 of the Copyright Law, and the procedure for granting royalties based on the Copyright Law is carried out through the Collective Management Institution (article 87), which will be distributed to the respective copyright holders.